New farming systems for Guyana's sandy soils - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
December 5-9-1988, at Georgetown, Guyana, to discuss 'Farming Systems for Low Fertility Acid, Sandy Soils'